Geological position and age of Tuxen-Rasmussen layered gabbroid intrusion (West Antarctica) - Mytrokhyn, O. V.; Bakhmutov, V. G.; Aleksieienko, A. G.; Gavryliv, L. I.; Mytrokhina, T. V. (Ukrainian Antarctic Journal, 2017)
The latest geological research carried out during seasonal work in 2017 revealed that metamorphosed layered gabbroids, which partially outcrop along the Antarctic Peninsula Coast on Cape Tuxen and Rasmussen Island, compose sheet-like intrusive body of total dimensions more than 3 km2. Significant part of the Tuxen-Rasmussen Gabbroid Intrusion (TRGI) is submerged under Waddington Bay. Main objectives of the study were the identification of geological position of the TRGI and the clarification of its geological age. In addition to the field methods of the geological research the samples collected during this and the previous years were studied using optical and electron microscopy techniques in order to identify petrographic and mineralogical features of the gabbroids. Results of the studies confirmed previous observation that TRGI was embedded in Upper Jurassic Volcanic Group (UJVG) of Antarctic Peninsula and it was responsible for contact metamorphism of the UJVG and suffered contamination by volcanic material. Gabbroids and volcanic rocks were later intruded by granites of Late Cretaceous age, which belong to the Andean Intrusive Suite (AIS) of Graham Land. Authors define geological age of TRGI as Early Cretaceous. Previous U-Pb isotope datings of the gabbroids are believed to be “rejuvenated”. It was discovered that TRGI strikes in northeastern direction and dips steep in northwestern direction. It is assumed that intrusive body continues underwater and can outcrop at the northern shore of the Waddington Bay and at Barros Rocks direction to the southwest. Petrographical researches showed that gabbroids underwent metamorphic alteration in conditions of epidote-amphibolite facies. They bear, nevertheless, relict structural-textural features and mineral associations of mafic igneous rocks. Authors drew a conclusion that geological position and petrographical peculiarities of TRGI correspond to hypabyssal level of crystallization. Primary igneous origin is proved for the microrhythmic layering of the gabbroids. Relict mineral associations allow to identify the rocks as olivine gabbro-norites. Potential Fe-Ti-V ore specialization is emphasized according to the revealed patterns of crystal fractionation and accumulation of ilmenite and magnetite.